2005
DOI: 10.1016/j.femsle.2005.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Bile salt and acid tolerance ofLactobacillus rhamnosusstrains isolated from Parmigiano Reggiano cheese

Abstract: This study aimed to compare phenotypic and genetic characteristics of Lactobacillus rhamnosus strains isolated at the end of the ripening of Parmigiano Reggiano cheese and to investigate an important prerequisite of probiotic interest, such as the capability to survive at low pH and in presence of bile salts. The use of API 50 CH, RAPD-PCR analysis and species-specific PCR allowed to ascertain the identity of 63 L. rhamnosus strains. Three L. rhamnosus strains isolated from Parmigiano Reggiano cheese, L. rhamn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(139 citation statements)
references
References 31 publications
6
126
2
5
Order By: Relevance
“…There is experimental evidence that some of the bacteria in Italian hard cooked cheese can have probiotic functions. In particular, it has been shown that, at 12 months of ripening, in Parmigiano Reggiano, the presence of Lactobacillus rhamnosus is still detectable, even if at low levels (10 3 -10 4 CFU/g), having the actual characteristics of probiotic (92). Also, Pancaldi et al (86) emphasise the probiotic nature of Parmigiano Reggiano and its possible use in the prevention of intestinal and extraintestinal diseases at all ages, from infants to the elderly.…”
Section: Probiotic Bacteriamentioning
confidence: 99%
“…There is experimental evidence that some of the bacteria in Italian hard cooked cheese can have probiotic functions. In particular, it has been shown that, at 12 months of ripening, in Parmigiano Reggiano, the presence of Lactobacillus rhamnosus is still detectable, even if at low levels (10 3 -10 4 CFU/g), having the actual characteristics of probiotic (92). Also, Pancaldi et al (86) emphasise the probiotic nature of Parmigiano Reggiano and its possible use in the prevention of intestinal and extraintestinal diseases at all ages, from infants to the elderly.…”
Section: Probiotic Bacteriamentioning
confidence: 99%
“…Bile salt tolerance Bile salt disorganize the structure of the cell membrane, and it is toxic for living cells (Succi et al, 2005).…”
Section: Tolerance To Acid-stressed Conditionsmentioning
confidence: 99%
“…Among the probiotic bacteria used in the manufacture of dairy beverages, L. rhamnosus GG is the most widely used. Owing to L. rhamnosus GG acid and bile resistance [56] Several factors have been reported to affect the viability of probiotic cultures in fermented milks. Acidity, pH, dissolved oxygen content, redox potential, hydrogen peroxide, starter microbes, potential presence of flavoring compounds and various additives (including preservatives) affect the viability of probiotic bacteria and have been identified as having an effect during the manufacture and storage of fermented milks [19,48,57].…”
Section: Drinkable Fresh Milk and Fermented Milksmentioning
confidence: 99%